Prognostic Impact of Minimal Pelvic Fluid in Locally Advanced Pancreatic Cancer: A Multicenter Retrospective Study - Lee, Jungnam; Park, Jin-Seok; Jeong, Seok; Lee, Don Haeng; Lim, Jung-Hyun; Cho, Soon Gu; Kwon, Chang Il; Hyun, Jong Jin; Choe, Jung Wan; Cho, Jae Hee; Jang, Sung Ill (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Minimal pelvic fluid (MPF) is occasionally encountered on computed tomography (CT) scans during the initial staging of newly diagnosed pancreatic cancer. However, its clinical relevance has scarcely been studied. This study intends to explore the incidence of minimal pelvic fluid and its relevance in terms of survival in locally advanced pancreatic cancer (LAPC) patients. Materials and Methods: The medical records of patients with LAPC at 4 tertiary referral institutions were retrospectively reviewed from January 2005 to December 2015. Minimal pelvic fluid was defined as a fluid collection volume in the pelvic cavity of <100 mL as determined by abdominal CT. The association between the presence of MPF and patient survival was evaluated. Results: A total of 59 patients (male:female, 33:26; median age, 68 years; range 46-82 years) with LAPC were enrolled. Of the 59 patients, 22.0% (n = 13) had MPF, and 78.0% (n = 46) had no pelvic fluid (NPF). Baseline clinical characteristics in the 2 groups, including extent of the tumor stage, extent of spread to the lymph nodes stage, and pattern of treatments, were not significantly different. However, median overall survival was significantly less in the MPF group [9.7 months, (95% CI, 5.9-13.5)] than in the NPF group as determined by the log-rank test [16.9 months, (95% CI, 9.3-24.5)] (P = .002), and univariate and multivariate analyses showed that the presence of MPF independently predicted a poor prognosis. Conclusion: The presence of MPF was found to be significantly associated with reduced survival and an independent poor prognostic biomarker in LAPC patients. Cite this article as: Lee J, Park J, Jeong S, et al. Prognostic impact of minimal pelvic fluid in locally advanced pancreatic cancer: A multicenter retrospective study. Turk J Gastroenterol. 2023;34(12):1249-1256.